Pengaruh Lingkungan Kerja, Motivasi Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada Upt Pengelolaan Sumber Daya Air Tumpang) - Erlyn Dwi Meganovitasari; Agus Widarko; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted on employees of the UPT Pengelolaan Sumber Daya Air Tumpang. This study aims to determine and analyze the influence of the work environment, work motivation, and work discipline on employee performance. This type of research is an explanatory research with a quantitative approach. The target population in this study were UPT Pengelolaan Sumber Daya Air Tumpang, amounting to 51 employees. The sampling technique used in this study is saturated sampling. Data collection methods used are by distributing questionnaires. Data analysis techniques used multiple linear regression analysis. The results of data analysis showed that the variables of the work environment, work motivation, and work discipline simultaneously affect employee performance. This can be proven by the magnitude of the F value of 0,000 (0,000 < 0.05). The work environment partially influences employee performance with a significance value of t of 0.002. Work motivation partially influences employee performance with a significance value of t of 0.020. Work discipline partially influences employee performance with a significance value of t of 0.032. Keywords: Work Environment, Work Motivation, Work Discipline, Employee Performance